1998
DOI: 10.1007/bf02802026
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in the brain

Abstract: The rat adrenal hormone corticosterone reaches the brain and binds to intracellular receptors. These receptors comprise high-affinity mineralocorticoid and lower-affinity glucocorticoid receptors that, upon activation, affect the transcription rate of specific genes. The two receptor types are discretely localized in the brain, with particularly high expression levels in the hippocampus. Here we review recent studies showing that electrical properties and structural aspects of hippocampal principal neurons are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 136 publications
0
30
0
Order By: Relevance
“…So, glutamate signaling may also contribute to glucocorticoid-mediated spine plasticity (Karst et al, 2005, de Kloet et al, 2008). Activation of MR enhances excitability of hippocampal CA1 neurons whereas GR activation depresses their excitability (Joels and de Kloet, 1989, Joels and Vreugdenhil, 1998). Corticosterone, when applied to the dorsal hippocampus, depresses NMDA receptor-mediated LTP in a dose-dependent and GR-dependent fashion.…”
Section: The Neuro-endocrine Circuit Of Stress Is a Major Targetmentioning
confidence: 99%
“…So, glutamate signaling may also contribute to glucocorticoid-mediated spine plasticity (Karst et al, 2005, de Kloet et al, 2008). Activation of MR enhances excitability of hippocampal CA1 neurons whereas GR activation depresses their excitability (Joels and de Kloet, 1989, Joels and Vreugdenhil, 1998). Corticosterone, when applied to the dorsal hippocampus, depresses NMDA receptor-mediated LTP in a dose-dependent and GR-dependent fashion.…”
Section: The Neuro-endocrine Circuit Of Stress Is a Major Targetmentioning
confidence: 99%
“…There is accumulating evidence that corticosteroids, in addition to corticotropin releasing factor, play an important role in stress and the pathophysiology of anxiety disorders and depression [11,12]. It has been suggested that a disturbed HPA axis regulation may be a primary causal factor in depression.…”
Section: The Glucocorticoid Receptor and Its Role In The Central Strementioning
confidence: 99%
“…In the brain, they bind to two different intracellular receptors, the mineralocorticoid receptor (MR) and the glucocorticoid receptor (GR). MRs and GRs are co-located in brain regions that are involved in the regulation of fear and anxiety, such as hippocampus, septum, and amygdala [11,12]. Moreover, GRs are widely distributed in other parts of the brain, both in neurons and glia cells.…”
Section: The Glucocorticoid Receptor and Its Role In The Central Strementioning
confidence: 99%
See 2 more Smart Citations